The intrapreneur : confessions of a corporate insurgent - Bulloch, Gib, ....- (London : Unbound, 2018)
Today, over half of the largest economies in the world are global businesses - controlled by the few, and impacting the many. Business clearly has the power to change the world - but what if we, as individuals, had the power to change the world of business? For over a decade, Gib Bulloch led a corporate guerrilla movement within one of the world's largest global consulting organisations. Against the odds, he created a not-for-profit inside one of the most profit driven corporations in the world. Plaudits, prizes and promotions followed. But success came at a price: It ultimately cost him his job, his health and perhaps even his sanity as he found himself the unlikely resident of a psychiatric hospital in Glasgow. The Intrapreneur is an honest and insightful critique of the craziness of today's business environment - and a call to action for a new breed of social activist working within, about to join or completely disillusioned by today's business world. Finding your purpose... can feel like losing your mind.
Includes bibliographical references.
Keywords: Business enterprises; Ondernemen ; intern ondernemerschap; Social action; Social responsibility of business; Success in business